Patient involvement in assessing consultation quality: a quantitative study of the Patient Enablement Instrument in Poland. - Pawlikowska TRB; Walker JJ; Nowak PR; Szumilo-Grzesik W (Health Expectations, 2010)
Background Promoting a more patient-responsive service has been the focus of policy initiatives in newer EU states. One measure of success should be the patient's assessment of their consultation with their doctor. Objectives To measure consultation quality in Polish primary care using patient enablement (a patient-driven instrument developed in the UK) and to test its theoretical framework. To compare the patient enablement outcome of different types of doctor delivering primary care in Poland following reform. Design Cross-sectional quantitative questionnaire survey. Setting Random sample of primary care doctors practising within a 60-km radius of Gdansk, Poland. Subjects and outcome measures Patient Enablement Instrument and correlates were measured in 7924 consecutive adult consultations of 48 doctors, stratified according to training: family medicine specialists (diploma holders), non-diplomates and general medicine doctors (polyclinic internists). Results Completion was high (78%). The mean patient enablement score in Poland was 4.0 (SD 3.3) and mean consultation length was 10.3 min (SD 5.4 min). Consultation length and knowing the doctor are independently related to patient enablement in the Polish context. Variation between doctors is significant, but earlier differences in enablement between alternative providers have largely been ameliorated in practice. Conclusion It is feasible to use patient enablement on a large scale at routine consultation in primary care in Poland: acceptability was good in diverse environments. The internal consistency of enablement and its relationships broadly mirror those found in the UK. The effect of patient expectations shaped by social and cultural issues influencing enablement outcome requires further investigation.